2018
DOI: 10.3390/nu10010061
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Physical Fitness, Body Composition, and Nutrition Are Associated with Bone Status in University Students

Abstract: Understanding the modifiable factors that improve and maximize peak bone mass at an early age is necessary to design more effective intervention programs to prevent osteoporosis. To identify these modifiable factors, we analyzed the relationship of physical activity (PA), physical fitness, body composition, and dietary intake with bone stiffness index (SI), measured by quantitative ultrasonometry in young university students (18–21 years). Moderate-to-vigorous PA (MVPA) was the strongest predictor of SI (β = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 45 publications
0
21
2
Order By: Relevance
“…University life usually coincides with the transition between adolescence and adulthood, which is crucial in establishing habits that will be maintained throughout life [ 13 ]. Students who are more physically active and with better physical fitness exhibit better health-related quality of life [ 14 ], health parameters [ 14 , 15 ] and academic performance [ 16 ]. In addition, being physically unfit at a young age could also result in a greater risk of disability thirty years later [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…University life usually coincides with the transition between adolescence and adulthood, which is crucial in establishing habits that will be maintained throughout life [ 13 ]. Students who are more physically active and with better physical fitness exhibit better health-related quality of life [ 14 ], health parameters [ 14 , 15 ] and academic performance [ 16 ]. In addition, being physically unfit at a young age could also result in a greater risk of disability thirty years later [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies identified a small but significant positive relationship between calcium intake and BMD or QUS indices [24,46,47,48]. One study found that subjects taking cheese regularly had a significantly higher BMD compared with non-takers [26], highlighting the importance of dairy product besides milk as a source of calcium to maintain bone health.…”
Section: Resultsmentioning
confidence: 99%
“…The studies were performed in various countries and regions. The majority of the studies are from Saudi Arabia [ 15 , 17 , 18 , 19 ], Sri Lanka [ 20 ], Canada [ 21 , 22 , 23 , 24 ], Thailand [ 25 , 26 ] and South Korea [ 27 , 28 , 29 , 30 ], Jordan [ 31 , 32 ], Malaysia [ 33 , 34 ], China [ 35 , 36 ] and the rest are from United States [ 35 ], Nigeria [ 4 ], Taiwan [ 37 ], Syria [ 38 ], India [ 39 ], Poland [ 40 ], Denmark [ 41 ], U.K. [ 42 ], Iran [ 43 ], Pakistan [ 44 ], Columbia [ 45 ], the Basque region (Spain) [ 46 ], Japan [ 47 ] and Australia [ 48 ]. Most of the studies included in this review used either self-designed or validated questionnaire to assess the knowledge, attitude and practice among subjects regarding bone health/osteoporosis.…”
Section: Resultsmentioning
confidence: 99%
“…Bone mineral content and structure, besides being affected by genetics, hormones, and nutrition, are influenced by physical activity (PA) [6,7]. Impact loading, which is inherent in many sports, plays an important role in skeletal growth and shaping [8].…”
Section: Introductionmentioning
confidence: 99%